Key Strategies Toward Sustainable Social Housing Stock Development in Vietnam - Vu, Phuong Ngan; Thieu, Thi Thanh Thuy (International Journal of Sustainable Construction Engineering and Technology, 2025)
In response to its commitment to Sustainable Development Goal 11, the government of Vietnam has launched an ambitious national programme aiming to deliver one million social housing units for low-income groups and industrial park workers by 2030. While the quantitative target is clear, the qualitative dimensions of sustainability—covering economic, social, and environmental aspects—remain under-addressed. This study provides a comprehensive assessment of Vietnam’s social housing development, drawing on national data, regional case studies, and policy analyses. It systematically identifies 20 key barriers to sustainable social housing development, categorised under three pillars of sustainability, and evaluates their implications for practice and governance. In response, seven strategic directions are proposed, including financial incentives, regulatory reform, private sector engagement, and green technology adoption. The findings emphasise the need for a more integrated, inclusive, and adaptive housing strategy to close the gap between policy targets and implementation realities. This study contributes to the evolving discourse on affordable housing by aligning national efforts with global sustainability agendas, while offering practical insights for improving housing equity, resilience, and long-term viability in Vietnam.